High Prevalence of Gastrointestinal Manifestations of COVID-19 Infection in Hospitalized Patients With Cancer. Issue 1 (January 2021) - Grover, Shilpa; Redd, Walker D.; Zhou, Joyce C.; Nije, Cheikh; Wong, Danny; Hathorn, Kelly E.; McCarty, Thomas R.; Bazarbashi, Ahmad N.; Shen, Lin; Chan, Walter W.
Abstract : Background and Aim: Gastrointestinal (GI) symptoms have been reported with SARS-CoV-2 infection, but data on the prevalence and severity of GI symptoms in patients with cancer are limited. We sought to characterize the GI manifestations of coronavirus disease-19 (COVID-19) in oncology patients. Materials and Methods: We performed a multicenter cohort study of adult patients hospitalized with COVID-19 in 9 Massachusetts medical centers and identified those with an active malignancy. We evaluated the prevalence and severity of GI symptoms among hospitalized COVID-19 patients with cancer. Results: Of 395 hospitalized patients with COVID-19, 36 (9%) had an active malignancy. Of the 36 cancer patients, 23 (63%) reported ≥1 new GI symptom. The most prevalent symptoms were anorexia (12, 52%), diarrhea (9, 39%), and vomiting (8, 35%). GI symptoms were the initial symptom in 4/36 (11%) patients, were the predominant symptom in 5/36 (14%) patients, and were severe in 4/23 (17%) patients. Four of 5 patients with GI symptoms at presentation reported concurrent fever; notably 1 patient had no fever or respiratory symptoms. Twelve (33%) patients had elevations in liver transaminases at presentation; patients with elevated transaminases were more likely to have associated GI symptoms (83% vs. 54%, P =0.04). Conclusions: Acute GI symptoms associated with COVID-19 are highly prevalent in hospitalized cancer patients and can occur as a presenting symptom without respiratory symptoms. Symptoms are severe in a small subset of patients.